Report of stray sightings of Dendrelaphis proarchos (Wall, 1909) (Serpentes: Colubridae) in Surat, Gujarat, western India - Parmar, Dikansh S.; Thakur, Mehul N.; Agarwal, Ishan; Ganesh, S.r.; Vogel, Gernot (Zootaxa, 2024)
We here report on likely human-mediated, stray sightings of Dendrelaphis proarchos (Wall, 1909) in an unnatural range—Surat, Gujarat in western India. This population shows the following characters: (1) vertebral scales distinctly enlarged, larger than the dorsals of the first row; (2) 185–194 ventrals; (3) 139–142 divided subcaudals in complete tails; (4) 15 dorsal scale rows at midbody; (5) cloacal shield undivided; (6) one loreal scale; (7) three supralabials touching the eye; (8) a moderate first sublabial that touches two infralabials; (9) 11–12 temporal scales; (10) preoculars 1 or 2; (11) two or three postoculars; (12) maximum total length 1150 mm; (13) interparietal spot absent; (14) a black temporal stripe that does not starts on the postnasal or loreal but starts on the center of the eye follows postoculars (middle or second postocular) covers the majority of the temporal region and extends onto the neck; (15) a distinct, bright ventrolateral stripe bordered by one black line at the bottom; (16) dorsal interstitial color blue and (17) tongue color red with black tip. Data from a partial fragment of the mitochondrial 16S gene also reveal genetic congruence with published sequences from Sagaing and Ayeyarwady in Myanmar and Mizoram, India, further attesting the morphological conclusions. Absence of any sighting of this form in the wild despite long-term (> 15 years) studies in south Gujarat by us, the lack of previous reports of this population especially in natural habitats in Gujarat by colleagues, and reports of many such stray populations of non-native herpetofauna in the coastal port city of Surat together, indicate an unnatural, probably human-mediated, transportation of D. proarchos to Surat. Such likely human-mediated introductions of species outside their native range are a cause for concern and require awareness campaigns among snake rescuers not to ‘release’ such snakes in the Gujarat forests, but to keep them in zoos or return to the actual point of wild origin, if known or feasible.